Nature and history in modern Italy - Armiero, Marco, 1966-; Hall, Marcus, 1959- (Ohio University Press series in ecology and history., 2010)
Is Italy il bel paese-the beautiful country-where tourists spend their vacations looking for art, history, and scenery? Or is it a land whose beauty has been cursed by humanity's greed and nature's cruelty? The answer is largely a matter of narrative and the narrator's vision of Italy. The fifteen essays in Nature and History in Modern Italy investigate that nation's long experience in managing domesticated rather than wild natures and offer insight into these conflicting visions. Italians shaped their land in the most literal sense, producing the landscape, sculpting its heritage, embedding.